CircPTK2 Suppresses the Progression of Gastric Cancer by Targeting the MiR-196a-3p/AATK Axis - Gao, Ling; Xia, Tingting; Qin, Mingde; Xue, Xiaofeng; Jiang, Linhua; Zhu, Xinguo (Frontiers in Oncology, 2021)
Background: Gastric cancer is a type of malignant tumor with high morbidity and mortality. It has been shown that circular RNAs (circRNAs) exert critical roles in gastric cancer progression via working as microRNA (miRNA) sponges to regulate gene expression. However, the role and potential molecular mechanism of circRNAs in gastric cancer remain largely unknown. Methods: CircPTK2 (hsa_circ_0005273) was identified by bioinformatics analysis and validated by RT-qPCR assay. Bioinformatics prediction, dual-luciferase reporter and RNA pull down assays were used to determine the interaction between circPTK2, miR-196a-3p, apoptosis-associated tyrosine kinase 1 (AATK). Results: The level of circPTK2 was markedly downregulated in gastric cancer tissues and gastric cancer cells. Upregulation of circPTK2 significantly suppressed the proliferation, migration and invasion of gastric cancer cells, while circPTK2 knockdown exhibited opposite effects. Mechanically, circPTK2 could competitively bind to miR-196a-3p and prevent miR-196a-3p to reduce the expression of AATK. In addition, overexpression of circPTK2 inhibited tumorigenesis in a xenograft mouse model of gastric cancer. Conclusion: Collectively, circPTK2 functions as a tumor suppressor to suppress gastric cancer cell proliferation, migration and invasion through regulating miR-196a-3p/AATK axis, suggesting that circPTK2 may serve as novel therapeutic target for gastric cancer.